Effect of nicotine on biofilm formation of Streptococcus mutans isolates from smoking and non-smoking subjects. Issue 1 (1st January 2019) - El-Ezmerli, Nasreen F.; Gregory, Richard L.
ABSTRACT: Objectives : To investigate effects of nicotine on biofilm formation of Streptococcus mutans isolates from oral washes of smoker and non-smoker human subjects. Materials and methods : This study was conducted using 60  S. mutans isolates with three S. mutans isolates collected from oral washes of ten smoking subjects and ten from non-smoking subjects. Biofilm was formed by culturing each S. mutans strain (10 μl) in 190 μl of TSB supplemented with 1% sucrose (TSBS) containing 0, 0.25, 0.5, 1.0, 2.0, 4.0, 8.0, 16.0, and 32.0 mg/ml of nicotine for 24 h in 5% CO2 at 37°C in 96 well microtiter plates. The absorbance values of biofilm were measured at 490 nm in a microplate spectrophotometer. Results : There was a significant effect (p-value < 0.05) of nicotine concentrations and smoking on the growth of biofilm, planktonic cells, and total absorbance, for all strains of S. mutans . Isolates from smokers had significantly more biofilm at 0–16 mg/ml of nicotine compared to those from non-smokers (p-value < 0.0001). Conclusion : S. mutans smoker isolates are more affected by high nicotine concentrations than non-smoker isolates. Clinical Relevance : The use of nicotine products increases the growth of S. mutans and may place tobacco users at risk for dental decay.